Uncovering Justice as a New Dimension of Islamic Leadership: A Hybrid Systematic Literature Review and Bibliometric Analysis - Syamsul Hadi; Jain Yassin; Utik Bidayati; Alifah Widya Rachmawati (Global Review of Islamic Economics and Business, 2026)
A multitude of inquiries have explored Islamic leadership over the past few decades. Nevertheless, the academic literature on this topic remains limited. Therefore, the present investigation seeks to conduct an organized academic assessment, combined with a bibliometric evaluation, of Islamic leadership, anchored in currently available observational data. This study employs a structured literature review as its primary investigative framework, using the keyword phrase "Islamic leadership" across "Article Titles, Abstracts, and Keywords" in the Scopus database, yielding a collection of 1,745 documents published between 1983 and 2025. This data extraction took place on January 31, 2025. Subsequently, the gathered information was subjected to a bibliometric examination utilizing the VOSviewer application. Research on Islamic leadership remains limited in non-Muslim-majority regions, with prior studies largely centered on countries such as Malaysia and Indonesia. Future research should expand to more diverse geographical contexts. Beyond bibliometric findings that emphasize ethical and performance-related themes, this study advances the theoretical framework by positioning justice (al-adl) as a core dimension of Islamic leadership, complementing the established prophetic traits of honesty (ash-shidq), trust (al-amanah), knowledge (al-fathanah), and communication (at-tabligh). In practice, the proposed framework provides guidance for organizations to embed ethical governance and equitable decision-making into leadership and HR practices. Socially, it supports policymakers and educators in promoting social cohesion and cross-cultural understanding. Overall, while Islamic leadership research is expanding globally, studies on its conceptual development and dimensional structure remain scarce. Originality – Research on Islamic leadership is growing globally. However, studies examining the development of Islamic leadership and its dimensions remain limited.